(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In recent years, the payments industry has gone through massive innovations. New technological modernization has brought significant changes in the eCommerce industry. Merchants and regulators are moving from traditional payments to real-time payment systems. Merchants now have a diverse array of payment model options with their distinct challenges and pricing structures. This research will prove handy for the merchants. It gives a deep knowledge and understanding of the three most common commercial and contractual models offered by Payment Service Providers (PSPs). These models are Payment Facilitation (PayFac), Integration-Only, and Merchant-of-Record Model (MoR). This research will enable the merchants to align smoothly and help them make informed decisions, eventually reducing business risks and catering to their needs.